The Moderating Role of Education Level in The Predictors of Entrepreneurial Behavior: A Study of Karnali Province, Nepal - K.C., Govinda (Journal of Economics and Management, 2025)
This study was designed to illustrate the importance of formal education in the process of entrepreneurship. This study investigates the moderating role of education level in relationship between entrepreneurial self-efficacy, expectancy-value belief, entrepreneurial environment, entrepreneurial intention, and entrepreneurial behavior Method, this is a quantitative study where data were collected using a structured questionnaire. Sample size of this study is 290, 165 respondents are with formal education and 125 with no formal education. This study uses Permutation Multi-Group Analysis (MGA) in PLS-SEM to look into how different levels of education, specifically having no formal education and a formal education, affect these relationships. Findings, the finding of this study suggested that formal education is plays significant role in translating intention in to behavior. Implication The results of this study is contribution to the theory of planned behavior. It shed light on how formal education impacts entrepreneurial intention and behavior, presenting important implications for policymakers, educators, and entrepreneurs.